AlGaN/GaN HEMT-based ultraviolet photodetectors with enhanced device efficiency - Ahmed Salah Hawash Razeen (Nanyang Technological University, 2024)
AlGaN/GaN HEMT structures have gained significant attention in recent years due to their wide range of applications in power and optoelectronics, including electric vehicles, environmental monitoring, and satellite communication. These structures possess excellent properties such as wide bandgap, high breakdown voltages, high power density, and high switching speeds, which make them highly suitable for diverse applications. Ultraviolet photodetectors (UV PDs) based on AlGaN/GaN HEMTs have exhibited exceptional performance characteristics such as high speed, low noise, and high response. However, the performance and reliability of these devices are limited by the presence of structural defects, which hindered their large-scale production. New and innovative solutions based on photonic nanostructures have been developed and proven to enhance the UV PDs performance, but most lack the feasibility and integrability with CMOS and HEMT fabrication process. In this regard, this thesis work focused on optimizing the AlGaN/GaN HEMT structures and surface modifications to enhance the performance of UV PDs. The study involved growing three different AlGaN/GaN HEMT structures using metal-organic chemical vapor deposition (MOCVD), and comparing their structural, optical, and electrical characteristics. The three HEMT structures differ in the buffer stack used, where one was grown with step-graded AlGaN buffer on Si (111) substrate, the second with AlGaN/AlN superlattice (SL) stack on Si (111) substrate, and the third with buffer-free structure on semi-insulating 4H-SiC substrate. The Hall mobilities for the step-graded, SL-based, and buffer-free structures were 1370 cm2/V.s, 1550 cm2/V.s, and 1530 cm2/V.s, respectively, and the sheet carrier concentrations were 8.8 ×10^12 cm^(-2), 1.08×10^13 cm^(-2), and 1.09×10^13 cm^(-2), respectively. The SL-based buffer structure exhibited the best two-dimensional electron gas (2DEG) characteristics and stress management ability, leading to superior HEMT device performance with remarkable drain current and transconductance of 406.3 mA/mm and 81.5 mS/mm, respectively. The fabrication and characterization of high performance self-powered and photoconductive UV PD devices were also demonstrated. Metal-semiconductor-metal (MSM) UV PDs with semi-transparent Schottky Ni/Au metal were fabricated on the HEMT structures with SL buffer on Si and with no buffer on 4H-SiC. The SL-buffer based devices demonstrated remarkable self-powered responsivity of 2.2 A/W and a specific detectivity of 5.8×10^10 Jones that surpassed the reported devices of the same structure and device architecture and are close to the overall state-of-the-art self-powered performance. Furthermore, the study investigated the use of periodic nanohole arrays to enhance the performance of UV PDs. Optical simulations were performed on periodic nanohole arrays with different lattice constants and depths, and the results showed that the wavelength selectivity and higher absorptance of UV light depend on the geometry of the nanoholes. The optimized simulation geometry of 230 nm period was used to fabricate MSM UV PD devices with 12 nm, 18 nm, and 40 nm deep nanohole arrays. All devices showed photodetection with selectivity of the 325 nm light, with enhanced performance than the unpatterned devices. The 40 nm deep nanohole patterned PD device showed peak responsivity of 1.4×10^5 A/W at 5 V applied voltage, which is two- and three-fold higher than other patterned and unpatterned devices, respectively. The UV/visible rejection ratio was also improved with nanohole patterning into the surface where the -3dB cut-off wavelength was found to be 365 nm, with the 40 nm deep nanoholes showing a rejection ratio of ~ 10^3. The role of nanohole arrays in enhancing the PD performance was studied and compared between all devices and was basically attributed to that the deeper nanoholes capturing more of the incident UV photons, prolonging their path into the GaN layer, and increasing the photocarrier generation. This thesis work thus presents a comprehensive study of the optimization of AlGaN/GaN HEMT structures and the application of nanophotonics for enhanced performance, power-efficient, and HEMT-compatible UV photodetectors.